(untitled) (Research, Society and Development, 2021)
This paper aims to present the expansion of Rudimentary schools in the state of Rio Grande do Norte between the years 1924 to 1930. The time frame is justified by the various changes in the organization of education in the North of Rio Grande do Norte, such as the creation of of the Department of Education, in 1924 and the approval of the Internal Regulations of the state schools. The following questions guide this investigation: How were Rudimentary Schools organized in Rio Grande do Norte? How did the expansion of Rudimentary schools in the state of Rio Grande do Norte occur between the years 1924 to 1930? Methodologically, documental analysis was adopted, according to Arostegui (2006), and for the treatment of these sources, we will rely on the understanding of Ragazzini (2001) and on the evidential method of Ginzburg (1989). The sources for this study are the Messages presented annually by the state governors to the Legislative Assembly, in addition to the educational legislation of the period and studies that address the same theme. In this sense, it is concluded that the concern with the dissemination of public instruction instituted an expansion of Rudimentary Schools, in which primary education was assisted through these in places where there were no school groups. The Rudimentary School was the type of school that expanded the most between 1924 and 1930 in Rio Grande do Norte.